OP0058 DEVELOPMENT OF INFLAMMATORY BOWEL DISEASE DURING TREATMENT WITH ETANERCEPT IN PATIENTSWITH JUVENILE IDIOPATHIC ARTHRITIS. (June 2019) - Krol, Roline; Swart, Joost F.; Giancane, Gabriella; Roock, Sytze De; Herlin, Troels; Dolezalova, Pavla; Sanner, Helga; Susic, Gordana; Sztajnbok, Flávio R.; Maritsi, D; Constantin, Tamas; Vargova, V; et al.
Abstract : Background: Juvenile idiopathic arthritis (JIA) has a reported prevalence varying from 16 to 150 per 100, 000 patients and it thereby is the most frequent chronic rheumatologic disease presenting in childhood. Inflammatory bowel disease (IBD) is an auto-inflammatory disease that can develop in patients with JIA. Results from multiple studies suggest an association between therapy with Etanercept (ETN) and occurrence of IBD in patients with JIA, which may or may not be counteracted by methotrexate. Objectives: The aim of this study was to describe characteristics of JIA patients who developed IBD and to evaluate a possible relationship between IBD onset and medication use at IBD onset. Methods: Pharmachild, the largest international JIA registry, was used for this study. Patients were enrolled via members of the Paediatric Rheumatology INternational Trials Organisation (PRINTO). The registry contains both retrospective and prospective data. Results: A total of 8, 309 patients were included in this study. 290 gastrointestinal disorders were reported in 260 patients. 50 cases in 47 patients were classified as IBD or suspected IBD. Age at JIA onset was significantly higher in patients who developed IBD (9.1 vs 7.1 years p=0.002), and female predominance was lower (48.9% versus 67.6% p=0.011). Enthesitis related arthritis (ERA) was the JIA subtype in 40.4% of the patients who developed IBD. In 14 out of 47 patients more detailed information about IBD disease onset was available, such as date of disease onset and medication used at that time. 71.4% of all 14 patients used etanercept and 50.0% used MTX 3 months prior or at IBD onset. Etanercept exposure prior to IBD onset varied from no exposure to 6.39 years with a median of 1.3 years. Methotrexate exposure prior to disease onset varied from no exposure to 8.10 years with a median of 2.9 years. Information regarding quality of life was available for 2, 752 patients of which 17 IBD patients. Quality of life, both physical and psychosocial, was significantly lower in patients who developed IBD patients (p=0.018 and p=0.046 respectively). Conclusion: In this study ERA patients were more at risk of developing IBD and 71.4% used etanercept while developing IBD. We did not find a protective role of MTX since 50.0% of patients with available data developed IBD while using MTX. Lastly, IBD has an important physical and psychosocial impact on quality of life. Reference: [1] Swart JF; Giancane G; Horneff G; Magnusson B; Hofer M; Alexeeva E; Panaviene V; Bader-Meunier B; Anton J; Nielsen S; De Benedetti F; Kamphuis S; Stanevicha V; Trachana M; Ailioaie LM; Tsitsami E; Klein A; Minden K; Foeldvari I; Haas JP; Klotsche J; Horne. Pharmacovigilance in juvenile idiopathic arthritis patients treated with biologic or synthetic drugs: combined data of more than 15, 000 patients from pharmachild and national registries. Arthritis Res Ther. 2018; Disclosure of Interests: Roline Krol: None declared, Joost F. Swart: None declared, Gabriella Giancane: None declared, Sytze De Roock: None declared, Troels Herlin: None declared, Pavla Dolezalova: None declared, Helga Sanner: None declared, Gordana Susic: None declared, Flávio R. Sztajnbok: None declared, D Maritsi: None declared, Tamas Constantin: None declared, V Vargova: None declared, Sujata Sawhney: None declared, Marite Rygg: None declared, SHEILA KNUPP DE OLIVEIRA: None declared, Marco Cattalini: None declared, Ellen Nordal: None declared, Claudia Magalhaes: None declared, Alberto Martini Consultant for: I do not have any conflict of interest to declare since starting from 1 March 2016 I became the Scientific Director of the G. Gaslini Hospital; therefore, my role does not allow me to render private consultancies resulting in personal income. I perform consultancy activities on behalf of the Gaslini Institute for the companies listed below: AbbVie, Biogen, Boehringer Ingelheim, Bristol-Myers Squibb, EMD Serono, Janssen, Novartis, Pfizer, R-Pharm. The money received for these activities are directly transferred to the Gaslini Institute's bank account. Before March 2016, I was the head of the Pediatric Rheumatology Department at the G. Gaslini Hospital, where the PRINTO Coordinating Centre is located. For the coordination activity of the PRINTO network, the Gaslini Hospital received contributions from the industries listed in this section. This money has been reinvested for the research activities of the hospital in fully independent manners besides any commitment with third parties., Nico Wulffraat: None declared, Nicolino Ruperto Grant/research support from: The Gaslini Hospital, where NR works as full-time public employee, has received contributions (> 10.000 USD each) from the following industries in the last 3 years: BMS, Eli-Lilly, GlaxoSmithKline, F Hoffmann-La Roche, Janssen, Novartis, Pfizer, Sobi. This funding has been reinvested for the research activities of the hospital in a fully independent manner, without any commitment with third parties., Consultant for: Received honoraria for consultancies or speaker bureaus (< 10.000 USD each) from the following pharmaceutical companies in the past 3 years: Ablynx, AbbVie, Astrazeneca-Medimmune, Biogen, Boehringer, Bristol-Myers Squibb, Eli-Lilly, EMD Serono, GlaxoSmithKline, Hoffmann-La Roche, Janssen, Merck, Novartis, Pfizer, R-Pharma, SanofiServier, Sinergie, Sobi and Takeda., Speakers bureau: Received honoraria for consultancies or speaker bureaus (< 10.000 USD each) from the following pharmaceutical companies in the past 3 years: Ablynx, AbbVie, Astrazeneca-Medimmune, Biogen, Boehringer, Bristol-Myers Squibb, Eli-Lilly, EMD Serono, GlaxoSmithKline, Hoffmann-La Roche, Janssen, Merck, Novartis, Pfizer, R-Pharma, SanofiServier, Sinergie, Sobi and Takeda.